MODEL KURIKULUM REKONTRUKSI SOSIAL: MENGUBAH KURIKULUM UNTUK MEWUJUDKAN MASYARAKAT YANG LEBIH ADIL DAN DEMOKRATIS - Lutfi Nurmaidah (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study aims to examine the implementation of the social reconstruction curriculum model in promoting a more just and democratic society. The main problem addressed is the low relevance of existing curricula to real social issues, such as inequality, marginalization, and the lack of democratic participation among students. The method used in this research is a literature review with a qualitative approach, analyzing various scholarly sources related to curriculum studies and critical education. The results indicate that the social reconstruction curriculum model serves as an effective alternative for integrating social issues into the learning process. This approach encourages students to think critically, participate actively, and develop social awareness toward issues in their communities. Furthermore, the role of teachers as facilitators is crucial in creating dialogical and reflective learning environments. Therefore, the implementation of a socially oriented curriculum has significant potential to foster socially conscious individuals who contribute to the development of a more democratic and equitable society.